Distinguishing Signal From Noise in Immunopeptidome Studies of Limiting-Abundance Biological Samples: Peptides Presented by I-Ab in C57BL/6 Mouse Thymus - Nanaware, Padma P.; Jurewicz, Mollie M.; Clement, Cristina C.; Lu, Liying; Santambrogio, Laura; Stern, Lawrence J. (Frontiers in Immunology, 2021)
Antigen presentation by MHC-II proteins in the thymus is central to selection of CD4 T cells, but analysis of the full repertoire of presented peptides responsible for positive and negative selection is complicated by the low abundance of antigen presenting cells. A key challenge in analysis of limiting abundance immunopeptidomes by mass spectrometry is distinguishing true MHC-binding peptides from co-eluting non-specifically bound peptides present in the mixture eluted from immunoaffinity-purified MHC molecules. Herein we tested several approaches to minimize the impact of non-specific background peptides, including analyzing eluates from isotype-control antibody-conjugated beads, considering only peptides present in nested sets, and using predicted binding motif analysis to identify core epitopes. We evaluated these methods using well-understood human cell line samples, and then applied them to analysis of the I-Ab presented immunopeptidome of the thymus of C57BL/6 mice, comparing this to the more easily characterized splenic B cell and dendritic cell populations. We identified a total of 3473 unique peptides eluted from the various tissues, using a data dependent acquisition strategy with a false-discovery rate of <1%. The immunopeptidomes presented in thymus as compared to splenic B cells and DCs identified shared and tissue-specific epitopes. A broader length distribution was observed for peptides presented in the thymus as compared to splenic B cells or DCs. Detailed analysis of 61 differentially presented peptides indicated a wider distribution of I-Ab binding affinities in thymus as compared to splenic B cells. These results suggest different constraints on antigen processing and presentation pathways in central versus peripheral tissues.